VIEWS ON THE THEOLOGICAL FOUNDATIONS OF GNOSEOLOGICAL ACTIVITY IN THE MIDDLE AGES ISLAMIC WORLD (Scientific journal of the Fergana State University, 2024)
The article analyzes the problem of reason in Islamic philosophy, axiological criteria of scientific activity, deterministic, dialectical linkage of the systematization of relations between religion and science, religion and philosophy, moral requirements to human activity, Islamic bases of attitude to science in Muslim culture.